Consumer’s Trust Social Media Marketing as a Moderation: Effect of Perceived Credibility of Product and Brand Resonance on Brand Loyalty - Oktavenia, Kadek Ayuk Riska; Martini, Ida Ayu Oka (Universitas Warmadewa, 2024)
The aim of this research is to identify the effect of perceived credibility of product and brand resonance on brand loyalty with consumer's trust social media marketing as a moderator. The population used in this research is all Else Corset consumers with an unknown population size. The sampling technique used is non-probability sampling which can be used is accidental sampling with a sample size of 96 respondents. This research uses several questionnaire methods as data collection. The questionnaire is a written list of questions, designed with reference to data measurement instruments to measure perceived credibility of product, brand resonance, and consumer's trust in social media marketing. One method for analyzing moderating variables is moderating regression analysis. Moderated regression analysis is a regression analysis that involves moderating variables in building a relationship model. The research results show that Perceived Credibility of Product has a positive and significant effect on Brand Loyalty. Brand Resonance has a positive and significant effect on Brand Loyalty. Customer's Social Media Marketing can strengthen the Perceived Credibility of Products in Brand Loyalty. Customer's Social Media Marketing is unable to strengthen the influence of Brand Resonance on Brand Loyalty. To increase brand loyalty, companies must focus on building product credibility through high-quality products, transparent communication, and expert support. In addition, Els Korset should utilize social media marketing to strengthen the positive impact of perceived product credibility on brand loyalty. However, companies should not rely solely on social media marketing to influence brand resonance, as this has a direct and significant impact on brand loyalty.